On‐the‐job training makes the difference: healthcare assistants' perceived competence and responsibility in the care of patients with home mechanical ventilation. Issue 2 (2nd September 2014) - Swedberg, Lena; Michélsen, Hans; Hammar Chiriac, Eva; Hylander, Ingrid
<x xml:space="preserve">Abstract</x> Objectives To describe and analyse perceived competence and perceived responsibility among healthcare assistants (HC assistants), caring for patients with home mechanical ventilation (HMV) and other advanced caring needs, adjusted for socio‐demographic and workplace background factors. Design A cross‐sectional study was conducted including 128 HC assistants employed in Stockholm County, Sweden. Methods The HC assistants responded to a study‐specific questionnaire on perceived competence and perceived responsibility, provided socio‐demographic and workplace background data, as well as information on the patient characteristics for the understanding of their work situations. Descriptive statistics and logistic regression analyses were performed. Results Eighty per cent of the HC assistants rated their perceived competence as high, and fifty‐nine per cent rated their perceived responsibility as high. Fifty‐five per cent lacked formal healthcare training, and only one in five of the HC assistants had a formal training equivalent with a licensed practical nurse (LPN) examination. Males lacked formal training to a greater extent than females and rated their competence accordingly. On‐the‐job training was significantly associated with high ratings on both perceived competence and perceived responsibility, and clinical supervision was associated with high rating on perceived responsibility. Conclusions HC assistants with limited formal training self‐reported their competence as high, and on‐the‐job training was found to be important. Also, clinical supervision was found important for their perception of high responsibility. In Sweden, HC assistants have a 24‐hour responsibility for the care and safety of their patient with HMV and other advanced caring needs. The study results point out important issues for further research regarding formal training requirements as well as the needs for standardised workplace training and supervision of HC assistants. The consequences of transfer of responsibility by delegation from healthcare professionals to paraprofessionals within advanced home care also need further study.